Translating authentic technical documents in specialised translation classes - Anabel Galán-Mañas (JoSTrans: The Journal of Specialised Translation)
This article describes a learning experience which consists of adopting a project-based approach to translating authentic documents in a scientific-technical texts translation class. The aim is to provide students with the necessary competences so that they are able to work satisfactorily as a professional translator. From a constructivist perspective, working on authentic scientific-technical documents in a translation class provides students with a setting well suited to not only developing degree-specific competences, but also general competences, such as working in a team, autonomously or using information and communications technologies (ICT). Students perform better under this kind of approach because of the motivation factor: they deal with situations that crop up in the professional world, discover how other courses in their degree programme are inter-related, use ICT, work through the entire translation process and practice skills they will need to work as a professional translator.